Pengujian Papan Komposit Diperkuat Serat Tandan Kosong Kelapa Sawit ( TKKS ) Dengan Menggunakan Alat Uji Impact Charpy - Safrijal Safrijal; Syurkarni Ali; herdi susanto (universitas teuku umar, 2017)
The potential waste of empty fruit bunches palm oil (TKKS) that pure of utilization, so unusefull things. The composite combine Two phase that is the phase matrix and the reinforced phase. Polyester resin is one of the matrix and empty fruit bunches of oil palm as an reinforced. This case is Composite Board Test with a specimen size of 55 x 10 x 10 mm using impact test to be able to know the hardness result of resin mixture and empty fruit bunch palm oil, Composite fiber board is formed with brittle and rigid condition. In the composite test process using the impact test apparatus, the steps of the test there are lifting the pendulum up to 140 degrees by turning counterclockwise, positioning the specimen at the pedestal completely in the middle position, where the knife in the specimen pendulum parallel to the locked pendulum should be pressed on the brake pedal, Pull the pendulum lock or release to swing and break the specimen, Brake pedal is released to stop pendulum, View and record the test data result that indicated by the needle pointer on the arc, the final results shown average impact value is 0.467 J / mm2. In the Horizontal direction the results Average 0.491 J / mm2, highest Vertical direction value 0.480 J / mm2, and Horizontal direction 0,506 J / mm2Keywords : oil palm empty fruit bunch waste, economical products, compressive strenght of the material